Ghrelin/GHSR Axis Induced M2 Macrophage and Alleviated Intestinal Barrier Dysfunction in a Sepsis Rat Model by Inactivating E2F1/NF-κB Signaling - Lei Zhu; Zhimin Dou; Wei Wu; Qiliang Hou; Sen Wang; Ziqian Yuan; Bin Li; Jian Liu (Canadian Journal of Gastroenterology and Hepatology)
Sepsis is an inflammatory reaction disorder state that is induced by infection. The activation and regulation of the immune system play an essential role in the development of sepsis. Our previous studies have shown that ghrelin ameliorates intestinal dysfunction in sepsis. Very little is known about the mechanism of ghrelin and its receptor (GHSR) on the intestinal barrier and the immune function of macrophage regulation. Our research is to investigate the regulatory effect and molecular mechanism of the ghrelin/GHSR axis on intestinal dysfunction and macrophage polarization in septic rats. A rat model of sepsis was established by cecal ligation and puncture (CLP) operation. Then, the sepsis rats were treated with a ghrelin receptor agonist (TZP-101) or ghrelin inhibitor (obestatin). The results suggested that TZP-101 further enhanced ghrelin and GHSR expressions in the colon and spleen of septic rats and obestatin showed the opposite results. Ghrelin/GHSR axis ameliorated colonic structural destruction and intestinal epithelial tight junction injury in septic rats. In addition, the ghrelin/GHSR axis promoted M2-type polarization of macrophages, which was characterized by the decreases of IL-1β, IL-6, and TNF-α, as well as the increase of IL-10. Mechanistically, the ghrelin/GHSR axis promoted E2F2 expression and suppressed the activation of the NF-κB signaling pathway in septic rats. Collectively, targeting ghrelin/GHSR during sepsis may represent a novel therapeutic approach for the treatment of intestinal barrier injury.